2022
DOI: 10.1111/1755-0998.13596
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the evolution of the critically endangered soft‐shelled turtle Rafetus swinhoei

Abstract: River and Taihu Lake) and the Red River Basin (China and Vietnam) (Wang & Shi, 2011). It was especially abundant in the Red River basin in Yunnan Province (China) in the 1950s and 1960s, and new individuals were discovered each year even though the 1970s (Rao, 2017;Wang & Shi, 2011;. However, due to its uncertain taxonomic status, R. swinhoei was ignored for a long time until 1987 when the validity of the species was confirmed in Meylan's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 91 publications
3
11
0
Order By: Relevance
“…The high ratio of syntenic regions that we found is between chelonian taxa that diverged around 50 to 70 million years ago (mya) [ 104 ] (Fig. 2 ) and is in agreement with previous studies, where the base substitution rate (evolutionary rate) of chelonians was found to be relatively low ([ 105 , 106 ]; see [ 107 ]).…”
Section: Data Descriptionsupporting
confidence: 92%
“…The high ratio of syntenic regions that we found is between chelonian taxa that diverged around 50 to 70 million years ago (mya) [ 104 ] (Fig. 2 ) and is in agreement with previous studies, where the base substitution rate (evolutionary rate) of chelonians was found to be relatively low ([ 105 , 106 ]; see [ 107 ]).…”
Section: Data Descriptionsupporting
confidence: 92%
“…The high ratio of syntenic regions that we found are between chelonian taxa that diverged around 50-70 mya [93] (Fig. 2) and is in agreement with previous studies, where the base substitution rate (evolutionary rate) of chelonians was found to be relatively low (see [94]).…”
Section: Synteny Analysissupporting
confidence: 93%
“…Artificial breeding plays an important and positive role in the conservation of endangered turtle populations. Aside from the failure of artificial assisted breeding with 2 R. swinhoei (one female and one male; the female turtle died during artificial induction in 2019) [ 8 ], other turtle species have been successfully artificially bred. More successful species, such as Platuysternon megacephalum [ 9 ] and Mauremys mutica [ 10 ], have played an important role in the growth of turtle populations.…”
Section: Discussionmentioning
confidence: 99%